Grey Clustering Evaluation of Water Resources Carrying Capacity Based on Triangle Whitening Weight Function. (December 2018) - Gao, Hua; Sun, Linhao
Abstract: Water resources are an important component of the resource environment. The sustainable carrying capacity of water resources is an essential indicator for the comprehensive evaluation of regional sustainable development. This paper will select 17 water resources carrying capacity impact factors to establish a sustainable water resources assessment system. The grey clustering evaluation based on the triangle whitening weight function is used to obtain the objective evaluation results of water resources carrying capacity.